2006
DOI: 10.1309/6507kah8ev592mj4
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Simple, and Accurate Detection of K-ras Mutations From Body Fluids Using Real-Time PCR and DNA Melting Curve Analysis

Abstract: The K-ras oncogene is one of the most useful genetic markers in screening for the presence of cancers because it is largely involved in tumorigenesis. However, most mutationdetection techniques are generally unsuitable for routine use, especially due to their timeconsuming, labor-intensive, and sensitive natures. Accordingly, we attempted to establish a new technique for analysis of K-ras alterations at codons 12 and 13 from body fluid specimens with tumor DNA using realtime polymerase chain reaction (PCR) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Later, SYBR Green I became the most widely used DNA dye for real-time PCR applications because of cost efficiency, generic detection of amplified DNA, and its ability to differentiate PCR products by melting curve analysis [ 8 , 9 ]. SYBR Green I has been applied in post real-time PCR melting curve analysis for rapid detection of various organisms, including Vibro vulnificus [ 10 ], Leptonema illini [ 11 ] and Plum pox virus [ 12 ], for mutations in the human K-ras gene [ 13 ] and for measurement of cell number in microtitre plate cultures [ 14 ]. SYBR Green I remains widely used despite numerous studies demonstrating its disadvantages such as extensive optimization [ 15 , 16 ], inhibition of PCR in a concentration-dependent manner [ 9 , 17 ], effects on DNA melting temperature [ 9 , 18 ], and preferential binding to certain DNA sequences [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Later, SYBR Green I became the most widely used DNA dye for real-time PCR applications because of cost efficiency, generic detection of amplified DNA, and its ability to differentiate PCR products by melting curve analysis [ 8 , 9 ]. SYBR Green I has been applied in post real-time PCR melting curve analysis for rapid detection of various organisms, including Vibro vulnificus [ 10 ], Leptonema illini [ 11 ] and Plum pox virus [ 12 ], for mutations in the human K-ras gene [ 13 ] and for measurement of cell number in microtitre plate cultures [ 14 ]. SYBR Green I remains widely used despite numerous studies demonstrating its disadvantages such as extensive optimization [ 15 , 16 ], inhibition of PCR in a concentration-dependent manner [ 9 , 17 ], effects on DNA melting temperature [ 9 , 18 ], and preferential binding to certain DNA sequences [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dieterle et al reported ratios of K-RAS mutant:WT DNA ranged over four orders of magnitude (10 0 -10 -4 ), with the median at approximately 10 -2 [78]. Additional indirect evidence that tumors contain K-RAS mutant subpopulations comes from studies that compare a sensitive mutation detection approach to standard DNA sequencing and report higher numbers of K-RAS-positive tumors using the more sensitive methodology [80,81]. For example, Beau-Faller et al detected a subset of K-RAS-positive tumors using a peptide nucleic acid-mediated PCR clamping technique that were K-RAS negative by DNA sequencing, even though the samples were characterized as having a sufficient percentage of tumor cells for DNA sequencing ana lysis [79].…”
Section: Nature Of Tumor-associated Mutations Methodologies For Mutamentioning
confidence: 99%
“…Melting of PCR product and anchor probe is monitored as fluorescence, with specific K-RAS mutations identified by Tm 10 -3 No [81] Capillary PCR with peptide nucleic acid clamp/sensor probe Capillary PCR performed with a peptide nucleic acid complementary to the wild-type sequence and spanning codons 12 and 13 of K-RAS reduces wild-type amplification and acts as sensor probe in melting temperature ana lysis 10 -4 No [13] Enriched-PCR/RFLP Multiple rounds of PCR and digestion of WT K-RAS codon 12, followed by direct sequencing NSR No [14] Real-time PCR with peptide nucleic acid clamp…”
Section: Mutant Cells/1 ML Of Bloodmentioning
confidence: 99%